Proceedings of the University of Muhammadiyah Malang's 1st International Conference of Mathematics Education (INCOMED 2017) 2018
DOI: 10.2991/incomed-17.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and The Application of Constructivism Learning: What Their Relationship is

Abstract: Educational expert is teachers. Teachers need the skills to implement their work optimally. The skills have several standards, one of them is the competence of practice. The competence of practice is how the teacher implements the learning process effectively. Effective learning will occur if the learning method used in suitable with the needs of students. Students need a teacher who can facilitate learning. Learning can be done in various ways, namely by using habits, reinforcement, even from within yourself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Surprisingly, none of the students reported that they opened the application for pedagogical purposes, more particularly for English language learning purposes; it is to be borne in mind that the information they searched on TikTok had nothing to do with improving their English communication skills. This finding is consistent with the finding of the study conducted by Pratiwi et al (2021). The students in the Pratiwi et al (2021) study reported that they used TikTok for the following two purposes: information searching (e.g., to look for information pertaining to life hacks and recommended skincare) and entertainment (i.e., they opened TikTok to entertain themselves).…”
Section: Free Tuitionsupporting
confidence: 89%
See 3 more Smart Citations
“…Surprisingly, none of the students reported that they opened the application for pedagogical purposes, more particularly for English language learning purposes; it is to be borne in mind that the information they searched on TikTok had nothing to do with improving their English communication skills. This finding is consistent with the finding of the study conducted by Pratiwi et al (2021). The students in the Pratiwi et al (2021) study reported that they used TikTok for the following two purposes: information searching (e.g., to look for information pertaining to life hacks and recommended skincare) and entertainment (i.e., they opened TikTok to entertain themselves).…”
Section: Free Tuitionsupporting
confidence: 89%
“…This finding is consistent with the finding of the study conducted by Pratiwi et al (2021). The students in the Pratiwi et al (2021) study reported that they used TikTok for the following two purposes: information searching (e.g., to look for information pertaining to life hacks and recommended skincare) and entertainment (i.e., they opened TikTok to entertain themselves). Although two of the students mentioned that they also looked for information about education on TikTok, none of them clearly stated that such information was related to English language learning.…”
Section: Free Tuitionsupporting
confidence: 89%
See 2 more Smart Citations